Persepsi guru tentang amalan pengurusan berasaskan sekolah, kecerdasan emosional dan kepimpinan instruksional pengetua sekolah agama menengah atas di Provinsi Banten Indonesia / Eneng Muslihah - Eneng, Muslihah (2011)
The rise and the fall of a nation depends upon its young generation. The destiny of the nation depends, among other things, depends further upon the quality of its generation, the better generation the better the nation is. The quality of young generation can be improved through education. The quality of education is influenced by many interrelated factors among of which are the qualification, competence, and performance of the school principals, teachers, administration staffs, and students as well.